ANALISIS KARAKTERISTIK MATERIAL ELEKTRODA TIP UNTUK PROSES LAS TITIK PADA BODI MOBIL UNTUK RANGKA MEMPERPANJANG UMUR PAKAI - Effendi, Riki; Hendra, Franka (Talenta Publisher, 2022)
One of the important components in the process of spot welding or spot welding is electrode tip or better known asâ€eltip